Postwar transfer of resources abroad by Latin America (UN. ECLAC SantiagoCL, 1992)
Latin American countries were net exporters of vast amounts of financial resources to the developed countries in the late 1980's. As a result there is now a permanent drain of resources abroad, which compounds their difficulties in participating more actively in international trade and contributes, in turn, to a worsening of the severe domestic problems that hamper efforts to bring about changes in production patterns, state reform and the achievement of greater social equity.
DC